2020
DOI: 10.1016/j.jesp.2020.104028
|View full text |Cite
|
Sign up to set email alerts
|

Do you get us? A multi-experiment, meta-analytic test of the effect of felt understanding in intergroup relations

Abstract: , J-C. (in press). Do you get us? A multi-experiment, meta-analytic test of the effect of felt understanding in intergroup relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 55 publications
9
35
1
Order By: Relevance
“…Given that a growing body of research on metabeliefs shows that how ingroup members feel outgroup members view them has a role in intergroup relations (Frey & Tropp, 2006; Yzerbyt et al, 2009), how ingroup members believe outgroup members understand them is especially important. Livingstone et al (2020b) maintained that felt understanding has a distinguishing feature that differentiates it from metabeliefs in that it involves meta–meta perspective (Gillespie & Cornish, 2010; Laing et al, 1966). Investigating their claim with a separate target, consistent with attitudinal generalization hypothesis (H1), we found that felt understanding positively predicted intergroup outcomes in CIJ (cohabiting) and COJ (separate).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that a growing body of research on metabeliefs shows that how ingroup members feel outgroup members view them has a role in intergroup relations (Frey & Tropp, 2006; Yzerbyt et al, 2009), how ingroup members believe outgroup members understand them is especially important. Livingstone et al (2020b) maintained that felt understanding has a distinguishing feature that differentiates it from metabeliefs in that it involves meta–meta perspective (Gillespie & Cornish, 2010; Laing et al, 1966). Investigating their claim with a separate target, consistent with attitudinal generalization hypothesis (H1), we found that felt understanding positively predicted intergroup outcomes in CIJ (cohabiting) and COJ (separate).…”
Section: Discussionmentioning
confidence: 99%
“…According to Livingstone et al (2020b), to the extent that felt understanding concerns “our” perspectives with “their” perspectives, it shares common ground with metaperceptions. However, felt understanding goes beyond this in significant ways because it contains views about how members of another group view one’s own (or the ingroup’s) viewpoints.…”
Section: Felt Understanding and Intergroup Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These items are designed to gauge people's attitudes and emotions toward a political object or organization [17,18]. From the perspective of intergroup orientation, the feeling thermometer is frequently used not only to estimate the perception of the outgroup, but also the representations of intergroup relations, generally in an environment where intergroup contact is effective [19]. Several studies have found that intergroup contact improves relationships between people from different groups.…”
Section: The In-group Feeling Thermometermentioning
confidence: 99%